2021
DOI: 10.3847/2041-8213/abde47
|View full text |Cite
|
Sign up to set email alerts
|

Claimed Detection of PH3 in the Clouds of Venus Is Consistent with Mesospheric SO2

Abstract: The observation of a 266.94 GHz feature in the Venus spectrum has been attributed to phosphine (PH3) in the Venus clouds, suggesting unexpected geological, chemical, or even biological processes. Since both PH3 and sulfur dioxide (SO2) are spectrally active near 266.94 GHz, the contribution to this line from SO2 must be determined before it can be attributed, in whole or part, to PH3. An undetected SO2 reference line, interpreted as an unexpectedly low SO2 abundance, suggested that the 266.94 GHz feature could… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 52 publications
0
46
0
1
Order By: Relevance
“…Venus has recently fueled significant interests from the astrobiology community, with the putative discovery of phosphine (PH 3 ) by remote spectroscopy; PH 3 is a type of biosignature gas which has been attributed to Terran anaerobic life (Greaves et al, 2020), although admittedly few investigations have been undertaken to explore potential abiotic processes that could also produce this compound. This surprising detection has subsequently given rise to an ongoing debate centered around the detection and interpretation of potential PH 3 signatures in the atmosphere of Venus (Encrenaz et al, 2020;Snellen et al, 2020;Lincowski et al, 2021). The origin, evolution, and composition of the Venusian atmosphere is an enigma that will soon be revealed by DAVINCI.…”
Section: The Future In Planetary Mass Spectrometry and Life Detectionmentioning
confidence: 99%
“…Venus has recently fueled significant interests from the astrobiology community, with the putative discovery of phosphine (PH 3 ) by remote spectroscopy; PH 3 is a type of biosignature gas which has been attributed to Terran anaerobic life (Greaves et al, 2020), although admittedly few investigations have been undertaken to explore potential abiotic processes that could also produce this compound. This surprising detection has subsequently given rise to an ongoing debate centered around the detection and interpretation of potential PH 3 signatures in the atmosphere of Venus (Encrenaz et al, 2020;Snellen et al, 2020;Lincowski et al, 2021). The origin, evolution, and composition of the Venusian atmosphere is an enigma that will soon be revealed by DAVINCI.…”
Section: The Future In Planetary Mass Spectrometry and Life Detectionmentioning
confidence: 99%
“…More recently, the detection has been corrected down to peak concentrations of 5-10 ppb and a global concentration of 1-4 ppb by the authors from the original paper [42]. However, concerns about the spectral analysis [43], in particular that the PH 3 detection could be misidentified sulfur dioxide, have been raised [44][45][46], mostly because the absorption lines of PH 3 (266.94 GHz) and SO 2 (~267.5 GHz) are close. The original authors continued to insist that their analytical methods are correct, and that the phosphine detection is valid [47].…”
Section: The Claimed Detection Of Phosphinementioning
confidence: 99%
“…However, this is not the spectral range Greaves et al [2] used to detect phosphine. As the phosphine detection has been marred in controversy [42][43][44][45][46][47][48], an independent verification of the claimed PH 3 detection is warranted. Especially insightful would be if a different methodology could be employed, such as trying to detect phosphine in the infrared range of the spectrum.…”
Section: The Claimed Detection Of Phosphinementioning
confidence: 99%
“…Phosphine, proposed as a potential biosignature for exoplanets (Sousa-Silva et al, 2020), was reported as having been discovered in the venusian atmosphere (Greaves et al, 2020a(Greaves et al, , 2020b(Greaves et al, , 2020c(Greaves et al, , 2021. A spirited debate about the detection (Encrenaz et al, 2020;Snellen et al, 2020;Akins et al, 2021;Lincowski et al, 2021) has ensued. Much of the debate has centered on the analysis of the observations, the altitude range over which phosphine was detected, the instability of phosphine in the hydrogen-poor venusian atmosphere, and the lack of known mechanisms of its production (Bains et al, 2021b).…”
Section: Recent Developmentsmentioning
confidence: 99%